Role of immersive technologies in healthcare education during the COVID-19 epidemic. Issue 4 (November 2020) - Pears, Matthew; Yiasemidou, Marina; Ismail, Mohamed A; Veneziano, Domenico; Biyani, Chandra Shekhar
The unparalleled epidemic of the novel coronavirus (COVID-19), during early December 2019 in Wuhan, China, has rapidly evolved into a global pandemic, became a matter of grave concern. The pandemic presented a unique challenge to government agencies worldwide. The paucity of resources and lack of knowledges to manage the pandemic, coupled with the fear of future consequences has established the need for adoption of emerging and future technologies to address the upcoming challenges. With introduction of measures to control the pandemic, trainees will see a dramatic decline in their in-person exposure to all aspects of their education, with no clear endpoint. This presents an extreme challenge for educators and, given the rapidly evolving situation, there have not yet been training authorities recommendations. We propose several innovative solutions to deliver medical education while maintaining the safety of residents and educators.